Analysis of The Sensor Line on Line Follower Robot as an Alternative Transport The Tub Trash in The Shopping Center - Yurni Oktarina; M. Nawawi; Windy Gafrila Tulak (VOLT : Jurnal Ilmiah Pendidikan Teknik Elektro, 2017)
This is a line follower robot is a robot designed to assist humans in activities such as throw away trash in the shopping center. On robot sensors added a line that consists of photodiode and LED.  The robot will walk follows the path which has been given a different color (black and white) to be detected by the sensor lines at the location of the junk-filled tubs and tubs of the empty trash. The research aims to know the performance of the sensor lines and the movement of the robot with the research method using PID. The results of this study when the distance between the sensor and the surface of 5 cm – 7 cm then the performance of the sensor surface in distinguishing the line of black and white still work fine, while at a distance of 8 cm – 10 cm sensor line performance diminished. For setting the PID, P = 10 will result averaged a greater error value i.e. 9.9 so the robot will move fast but unstable, while P = 5 align the median value error – i.e. 8 so the robot will move stable (as black)